Consequences of late diagnosis paracoccidioidomycosis: case report - Joana A. B. Sousa; Raisa S. Sá; Erika M. Pereira
ABSTRACT INTRODUCTION: Paracoccidioidomycosis is an endemic fungal infection of great prevalence in Latin America. CASE REPORT: A 68-year-old male patient was referred to the Universidade Federal do Maranhão (UFMA) due to an ulcerated lesion with moriform appearance throughout the palate, with symptoms. The clinical diagnosis was squamous cell carcinoma and the incisional biopsy confirmed the diagnosis of chronic paracoccidioidomycosis. Grocott-Gomori and periodic acid Schiff (PAS) were used as special stains. CONCLUSION: It is important to observe the clinical characteristics of the lesion, as well as to clarify the population about this infection since health education is a fundamental step to prevent and diagnose the lesion.